The Effect of the Use of Addition Bag Board Media on the Learning Outcomes of Mathematics Subjects - Pitaloka, Piana; Sari, Wulan (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine whether the results of children's activities in the use of addition bag board media can improve student learning outcomes in mathematics subjects and to find out whether the use of addition bag board media can improve student learning outcomes in mathematics subjects in grade III SD Negeri 26 Pagar Alam city. This study used a type of quantitative research with a pre-experimental design. Data collection techniques include tests, observation, interviews, and documentation. The results of this study show an influence on improving student learning outcomes in mathematics subjects. The existence of this influence is confirmed from the results of the hypothesis using a paired sample t-test with SPSS data processing version 23 comparing a ttable with tcount if tcount > ttable (tcount 17,000> ttable 2,064) then Ho is rejected and Ha is accepted.